Perancangan Sistem Informasi Akademik Lembaga Kursus Demi Music Center - Hartono, Sugiarto (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Evolution of technology will bring companies to have appropriate information systems to boost their businesses. Computerized information system is also needed by training courses like Demi Music Center. Demi Music Center realizes that computerized academic information system will help to optimize their business process. The purpose of this research is to analyze the operational business processes and academic administration at the DMC to determine deficiencies and problems occurred, then to provide a draft proposal of the new system in the DMC.. The method used is the method of analysis and design. Data collection methods used in this study was a survey, interviews, and literature. Outcome of this research is a design of academic information system based on desktop application. System can generate report easily and manage the data. Implementation of computerized academic information system can leverage the performance and increase efficiency of business process at Demi Music Center.